CERDAS CERMAT MANAJEMEN POLA HIDUP SEHAT DAN BERSIH DI LINGKUNGAN SDN KUTAGANDOK 1 - Andyka Nugroho; Yayan Alpian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Background: Kutagandok Village is one of the villages in Kutaluya District. Population data for 2022, the education level is dominated by elementary and high school graduates. Parents' attention to their children's education is good enough, but more participation from parents is still needed to support their children's education so they don't drop out of school. Maintaining a Clean Lifestyle is a process that is carried out to get messages that are then conveyed using hand-washing health. With the Covid-19 virus, many children are affected by diseases, both viral and fever. Examination Clean lifestyle in students is an activity designed so that students maintain a clean lifestyle. Purpose: To prevent disease by washing hands regularly for a clean lifestyle. Methods: The research conducted was directly involved in teaching at the elementary school level. Result: This socialization activity for students was carried out on the basis of the low ability of students to maintain a clean life, this activity was attended by 56 students in grades 5 and 6. This Smart Careful began by sharing problems faced by students related to the low ability to maintain a healthy lifestyle Conclusion: The conclusion is that at this school students in grades 5 and 6 have not been able to implement a healthy lifestyle.